Design of Lipid Matrix Particles for Fenofibrate: Effect of Polymorphism of Glycerol Monostearate on Drug Incorporation and Release. Issue 2 (20th December 2013) - Xia, Dengning; Cui, Fude; Gan, Yong; Mu, Huiling; Yang, Mingshi
<x xml:space="preserve">Abstract</x> The effect of polymorphism of glycerol monostearate (GMS) on drug incorporation and release from lipid matrix particles (LMPs) was investigated using fenofibrate as a model drug. X‐ray powder diffraction and differential scanning calorimetry were used to study the polymorphism change of GMS and the drug incorporation in GMS matrix. When medium‐chain triglycerides (MCT) was absent, melted GMS was frozen to α‐form of GMS with drug molecularly dispersed, whereas β‐form of GMS was formed with part of drug crystallized out when the ratio of GMS/MCT in the lipid matrix was 2:1 (w/w). For LMP composed of GMS/MCT (2:1, w/w) prepared, GMS was in α‐form when the particles were in nanometer range, whereas GMS was in β‐form when lipid particles were in micrometer range. The model drug was molecularly dispread in α‐form lipid nanoparticles, whereas part of drug was expulsed out from microparticles because of the denser crystalline packing than α‐form of GMS, and caused a faster drug release from lipid microparticles than that from nanoparticles. During the storage, the transformation of GMS from α‐form into the more stable β‐form promoted drug expulsion and caused drug precipitation. In conclusion, the polymorphism of GMS is an important factor determining particle stability, drug incorporation, and the release of the drug from LMP. Critical attention should be paid on the investigation as well as control of the lipid polymorphism when formulating lipid‐based matrix particles. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:697–705, 2014